Strategi Coping Mahasiswa Tugas Akhir Program Studi Bimbingan Dan Konseling - Stefanus Lio; Kristinus Sembiring (ILIN Institute Makassar, 2019)
Final writing or thesis is indeed a burden that can cause stress for students. Various problems, difficulties and challenges they must face. For this reason, they should have the right coping strategies to deal with and overcome any problems that cause stress in their final writing.This study aimed to identify or investigate how guidance and counseling students are able to cope with their problems and life’s situation when they are doing their final writing or thesis. A descriptive method with Coping Responses Inventory-Adult Form (CRI-Adult) was used. Results revealed that the students capitalized on different coping strategies when they deal with the problems that came up when they are doing their final writing. In general, it could be noted that all respondents utilized problem focused coping (PFC) and emotion focused coping (EFC) in the level of average until well above average.